Clinical efficacy of intravaginal recombinant lysostaphin administration on endometritis in sows. Issue 3 (3rd January 2021) - Ye, Guizi; Huang, Jinjiang; Li, Guodong; Zhang, Jien; Sun, Yongxue; Zeng, Dongping; Bao, Wenbin; Zhong, Jiang; Huang, Qingshan
Abstract: Recombinant lysostaphin has been used for the treatment of cow endometritis and mastitis in China. To our knowledge, no scientific effort has been made to evaluate the efficacy of lysostaphin in sows with clinical endometritis. Lysostaphin, loaded in effervescent tablets that were completely foamed and dissolved within 30 min in the presence of water or body fluids and released active lysostaphin, were administered vaginally on endometritis sows in this study. The clinical recovery, bacterial clearance and reproductive performance of sows with endometritis were investigated. We found that the 400U dosage (400U lysostaphin/pill/time, repeat once on the third day, a total of two times, with 10% oxytetracycline uterine injection as a control) is the most effective treatment. Staphylococcus aureus was the most prevalent finding (34%, n = 188), followed by Streptococcus (32%, n = 181), Escherichia coli (19%, n = 104) and other bacilli (15%, n = 83) before treatment by drugs. Administration of lysostaphin resulted in an extremely significant ( p < .01) reduction in S. aureus (0.18 ± 0.25 from 4.57 ± 0.33) and Streptococcus (0.11 ± 0.14 from 3.88 ± 0.29), as well as a significant ( p < .05) reduction in E. coli (0.55 ± 0.42 from 3.11 ± 0.14). Mixed infections (83%) were predominant before treatment, in contrast to single infections (61%) after treatment. Large‐scale trials were conducted to verify the clinical efficacy of lysostaphin on sow endometritis. The average cure rate of 400u lysostaphin on sow endometritis(82.5%) was higher than the antibiotic group(72.17%). In addition, our results revealed that intravaginal administration of lysostaphin had no adverse effect on the reproductive performance of sows. Thus, this lysostaphin has potential application value as a new method alternative to antibiotics to treat endometritis in sows. Abstract : This study examined the effect of intravaginal administration of recombinant lysostaphin on clinical recovery, bacterial clearance, and reproductive performance in sows with clinical endometritis. The outstanding performance of lysostaphin may provide new insights in managing endometritis in sow.